The development of security monitoring system for parking area / Md Zaki Kamis - Kamis, Md Zaki (2003)
This report describes the developed hardware and software for parking area security system. This system can be used as a control system proposed for the parking area. In order to allow this system to function, all the devices must be connected to the computer via hardware interface. Microsoft Visual Basic software is used to develop the program that will control the devices. Photo sensors are used as controlling devices to detect the current position of car. When the sensors detect the current position of a car, the data will be then transferred to the PC and the process of automation was performed by using the developed Visual Basic program. A digital camera is also used in this project to provide security by monitoring the video image of certain places in the entrance and exit of the parking lot.